Pengaruh Umur Panen dan Penambahan inokulum terhadap Produktivitas Hijauan Kacang Tunggak (Vigna Unguiculata) sebagai pakan=The Effect of Harvesting Time and Inoculant Addition on Productivity Forage oftunggak Bean (Vign - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT The aim of this experiment were to evaluate the effects of harvesting time and addition inoculant, and its interaction on quality of Tunggak bean forage. 2x2x2 factorials experiment following a RCD with three replicates was performed. The 3 treatment factors were: Harvesting time factor (U)i.e Ua: ten days before the normal harvest day (60 days), U2: normal harvest day (70 days)